PROFIL STUDENTA – PRZYSZŁEGO NAUCZYCIELA JĘZYKA ANGIELSKIEGO NABYWAJĄCEGO PEŁNE KWALIFIKACJE ZAWODOWE NA STUDIACH MAGISTERSKICH - Michońska-Stadnik, Anna (Neofilolog, 2019)
In professional research literature learner identity, motivation and autonomy are frequently the focus of attention. Identity is believed to be responsible for beliefs and opinions about the process of language attainment. Although much more has been written on learner identity, teacher identity is usually marginalized. The study summarized in this paper focuses on students – future teachers of English (N=32)- who attend M.A. EFL seminars to obtain full teaching qualifications. The students were asked to give answers to seven questionnaire statements referring to their present teaching careers and their former studies. It appeared that students coming from educational backgrounds other than university frequently show gaps in knowledge of second language acquisition theory and practice. What is more, as the ELT seminars cater mostly for students from institutions outside the university, considerable remedial work is needed in order to make it possible to prepare the students to write their M.A. theses independently.